A case study of stakeholder perceptions of patient held records: the Patients Know Best (PKB) solution. (September 2016) - Bidmead, Elaine; Marshall, Alison
Introduction: Patients Know Best (PKB) provides a patient portal with integrated, patient-controlled digital care records. Patient-controlled personal health records facilitate coordinated management of chronic disease through improved communications among, and about, patients across professional and organisational boundaries. An NHS foundation trust hospital has used PKB to support self-management in patients with inflammatory bowel disease; this paper presents a case study of usage. Methods: The stakeholder empowered adoption model provided a framework for consulting variously placed stakeholders. Qualitative interviews with clinical stakeholders and a patient survey. Results: Clinicians reported PKB to have enabled a new way of managing stable patients, this facilitated clinical and cost effective use of specialist nurses; improved two-way communications, and more optimal use of outpatient appointments and consultant time. The portal also facilitated a single, rationalised pathway for stable patients, enabling access to information and pro-active support. For patients, the system was a source of support when unwell and facilitated improved communication with specialists. Three main barriers to adoption were identified; these related to concerns over security, risk averse attitudes of users and problems with data integration. Conclusions: Patient-controlled personal health records offer significant potential in supporting self-management. Digital connection to healthcare can help patients to understand their condition better and access appropriate, timely clinical advice.